Improved method of clinical assessment pelvic muscle functional activity, that are responsible for postural balance - Klymovytskyy, Roman; Tyazhelov, Olexiy; Goncharova, Larisa (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The development of degenerative-dystrophic process in the hip joint often leads to a disruption of the pelvic grid muscles, the main indicator of which is the ability to maintain a dynamic horizontal balance of the pelvis under conditions of single-leg standing. Objective: to improve the method of evaluation of the function of skeletal muscles of a person who are responsible for preserving the postural balance. Methods: scale of evaluation of functional activity of muscles is developed, which involves the use of well-known methods of clinical examination. In this analysis of indicators such as the pelvic angle and trunk during walking, the stability of single-leg standing, objective and subjective assessment of resistance, etc., makes it possible to comprehensively assess the degree of functional disorders of the muscles that are responsible for maintaining the postural balance. Results: validity of the indicated evaluation scale was studied according to the data of three groups of patients for 12 months. It has been established that the proposed assessment scale enables to objectively evaluate the functional state of the muscles responsible for the postural balance and can be used to dynamically monitor the process of rehabilitation of patients during treatment. It was found that in patients with coxarthrosis of ІІ–ІІІ stages, in the absence of treatment during the year, important decreases in the function of these muscles, and the use of conservative treatment does not contribute to its recovery. Endoprosthetics of the hip joint allows improving the function of the muscles responsible for the postural balance, although in some patients, muscle function impairment is determined within one year after surgery. Conclusions: the technique of ball assessment of the functional state of the muscles responsible for the postural balance is proposed, its efficiency and effectiveness are proved. This gives grounds for recommending it for an objective clinical evaluation of the functional state of the muscular system in patients with diseases and effects of hip injuries.